2021
DOI: 10.1088/1757-899x/1125/1/012119
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Involute Profile Error on Spur Gear Processed using Wire EDM

Abstract: Demand on high accuracy product are getting raised recently. Wire Electrical Discharge Machining (EDM) is one of non-conventional machining who can produce high accuracy product with two axis. By using sparks from electrical energy to erode material in conductive fluid, called electrode fluid. A spur gear with JIS B 1701:1973 standard has specific criteria, including dimension and mechanical tolerance. DIN 1.2378 is a medium carbon steel which is common to use as a gear in automotive industry. This martial is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Peng et al [7] analyzed the tooth profile deviation in the hobbing forming process base on the theory of gear meshing, and adjusted the hobbing process parameters for the deviation size. Yusron et al [8] performed a study analyzing how wire-cutting parameters, including pulse width, open circuit voltage, wire tension, and pulse current, affect the deviation of the straight-toothed cylindrical gear tooth profile through orthogonal experiments. Vishal et al [9] found that adjusting hobbing parameters can greatly impact the microgeometry deviation and average deviation of gears.…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al [7] analyzed the tooth profile deviation in the hobbing forming process base on the theory of gear meshing, and adjusted the hobbing process parameters for the deviation size. Yusron et al [8] performed a study analyzing how wire-cutting parameters, including pulse width, open circuit voltage, wire tension, and pulse current, affect the deviation of the straight-toothed cylindrical gear tooth profile through orthogonal experiments. Vishal et al [9] found that adjusting hobbing parameters can greatly impact the microgeometry deviation and average deviation of gears.…”
Section: Introductionmentioning
confidence: 99%